(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The study investigates the relationship between students’ behaviour at tertiary institutions, parenting style, and self-worth. The study is predicated on the idea that parenting style is a collection of attitudes based on how parents communicate and feel about their kids. Additionally, it was shown that self-worth has no correlation with permissive parenting but is favorably correlated with authoritative parenting and negatively correlated with authoritarian parenting. In order to enhance children’s behavior and well-being, this article suggests that government agencies and policymakers include organized parenting education into national and local development initiatives.